Classical liberalism and the industrial working class - Mingardi, Alberto, 1981- author.
1 online resource.
Keywords: "Thomas Hodgskin (1787-1869) is today a largely unknown figure, sometimes considered to be a forerunner of Karl Marx. Yet a closer look at Hodgskin's works reveals that he was actually a committed advocate of laissez-faire economics and enthusiastic about labor-saving machinery and the Industrial Revolution, with a genuine interest in the well-being of the working classes. This book places him in the tradition of classical liberalism, where he belongs-as a disciple of Adam Smith, but even less tolerant of government power than Smith was. The Economic Thought of Thomas Hodgskin will be of interest to advanced students and scholars in the history of economic thought, economic history and the history of political thought"--